2012
DOI: 10.1111/j.1095-8649.2011.03210.x
|View full text |Cite
|
Sign up to set email alerts
|

Species, sex, size and male maturity composition of previously unreported elasmobranch landings in Kuwait, Qatar and Abu Dhabi Emirate

Abstract: This paper presents data from the first major survey of the diversity, biology and fisheries of elasmobranchs in the Persian (Arabian) Gulf. Substantial landings of elasmobranchs, usually as gillnet by-catch, were recorded in Kuwait, Qatar and the Emirate of Abu Dhabi (part of the United Arab Emirates), although larger elasmobranchs from targeted line fisheries were landed in Abu Dhabi. The elasmobranch fauna recorded was distinctive and included species that are undescribed, rare and have a highly restricted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
65
4

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 68 publications
(73 citation statements)
references
References 26 publications
4
65
4
Order By: Relevance
“…The average size of females of this species was significantly larger than males and 37.3% of recorded landings were pregnant females. Moore et al (2012) reported similar results in Kuwait waters where females (mostly pregnant stage) dominated the landings.…”
Section: Length-weight Relationshipssupporting
confidence: 71%
See 4 more Smart Citations
“…The average size of females of this species was significantly larger than males and 37.3% of recorded landings were pregnant females. Moore et al (2012) reported similar results in Kuwait waters where females (mostly pregnant stage) dominated the landings.…”
Section: Length-weight Relationshipssupporting
confidence: 71%
“…The differences could be the result of several factors like fishing gear selectivity and/or sample size, regional differential growth based on habitat (Motta et al, 2005). Furthermore, R. oligolinx from this study attained a greater maximum size (93.0 cm TL) than previously reported from elsewhere (80 cm TL by Abdul Nizar et al, 1988; 70 cm TL by Compagno et al, 2005; 85 cm TL by Moore et al, 2012). The difference detected between size-frequency distributions of females and males is probably a consequence of sexual segregation, a general characteristic of shark populations that is normally associated with reproduction, migration or competition (Springer, 1967;Klimley, 1987;Stevens and Mcloughlin, 1991;Motta et al, 2005).…”
Section: Length-weight Relationshipscontrasting
confidence: 53%
See 3 more Smart Citations